Formation of Professional-Value Guidelines in the Future Specialists of Preschool Establishments Preparation - Lysenko, Oleksandra (Pedagogical Discourse, 2012)
The article presents the basic classification of values, the main ones are described. Conformities of formation of professional-value guidelines ​​in the sphere of higher pedagogical education are singled out. Formation of the hierarchy of professional-value guidelines of students are studied.